Assessement of the performance of rubber clones utilizing the selection index method - Paiva, João Rodrigues de; Gonçalves, Paulo de Souza; Rossetti, Adroaldo Guimarães (Pesquisa Agropecuaria Brasileira, 2014)
An assessement study of two-year-old rubber tree clones (Hevea spp.) was conducted utilizing four selection indexes. The characters considered were yield, plant height, stem diameter, bark thickness and diameter of the latex vessels. In a hypothetical selection of the best clones, the expected genetic gain was estimated. The four indexes showed the same clones as superior, although the bj values estimated were different in absolute and relative values. In selecting the best clones during the growth phase, genetic gain was not increased with inclusion of a large number of characters in the selection index. No advantages ware observed in utilizing the methodology of selection index over tandem selection or in utilizing the selection of two-year-old rubber trees.